2006
DOI: 10.2746/042516407x153048
|View full text |Cite
|
Sign up to set email alerts
|

Theophylline does not potentiate the effects of a low dose of dexamethasone in horses with recurrent airway obstruction

Abstract: Oral theophylline for 7 days did not improve the effects of a low dose of dexamethasone for the treatment of horses with RAO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…In a previous study, conducted by Cesarini et al. (2006) under similar conditions and evaluating the efficacy of oral dexamethasone (0.05 mg/kg bwt q.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, conducted by Cesarini et al. (2006) under similar conditions and evaluating the efficacy of oral dexamethasone (0.05 mg/kg bwt q.…”
Section: Discussionmentioning
confidence: 99%
“…(2004) reported that feeding impairs bioavailability. Thirdly, the formulations used were different: while powdered formulation was used herein, Cesarini et al. (2006) used an i.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data obtained from 319 equine asthma-affected horses were extracted from 32 studies, some of which investigated two or more drugs. Ten studies used antimuscarinic agents (eight used a systemic form and one an inhaled form, one used both) [29][30][31][32][33][34][35][36][37][38]; nine studies used b 2 -AR agonists (two used a systemic form and seven an inhaled form) [29,[39][40][41][42][43][44][45][46]; 13 studies used corticosteroids (nine used a systemic form and one an inhaled form, three used both) [31,32,35,36,[47][48][49][50][51][52][53][54][55]; three used methylxanthines via systemic administration [29,33,53]; three studies used chromones via inhalation [56][57][58]; two studies used furosemide via systemic administration [11,59]; and one study, including two clinical trials, used a PDE4 inhibitor via systemic administration [36]. Overall, the available inclusion criteria and populations' characteristics of the analysed studies were homogeneous.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Methylxanthine derivatives are non‐specific PDE inhibitors that have beneficial effects on lung function in horses with heaves but have low therapeutic index 239–243 . The potentiating effects of corticosteroids by low‐dose theophylline reported in asthmatics 244 was not observed in horses with heaves after short‐term administration 241 .…”
Section: Treatmentsmentioning
confidence: 99%